Conservation biogeography - foundations, concepts and challenges - Richardson, D; Whittaker, R (Wiley-Blackwell, 2010)
Conservation biogeography involves the application of biogeographical principles, theories, and analyses to problems regarding biodiversity conservation. The field was formally defined in 2005, and considerable research has been conducted in the ensuing 5 years. This editorial sets the context for 16 contributions in a special issues of Diversity and Distributions on developments and challenges in conservation biogeography. Papers are grouped into the following main themes: species distribution modelling; data requirements; approaches for assigning conservation priorities; approaches for integrating information from numerous disparate sources; special challenges involving invasive species; and the crucial issue of determining how elements of biodiversity are likely to respond to rapid climate change. One paper provides a synthesis of requirements for a robust conservation biogeography for freshwater ecosystems. Conservation biogeography is well poised to make a significant contribution to the process of providing policy makers with objectively formulated scenarios and options for the effective management of biodiversity. The editorial, and the papers in the special issue, deliberate on many of the exciting developments in play in the field, and the many complex challenges that lie ahead.